Ladder of power and freedom: A qualitative data collection tool to understand local perceptions of agency and decision-making. - Petesch, Patti; Bullock, Renee (2018)
The purpose of the tool is to provide meaningful contextual and comparative evidence of local men’s and women’s own assessments and interpretations of the levels of agency in their lives, and the key factors and processes that they perceive to shape their capacities for making important decisions. Agency refers to the capacity to make important decisions in one’s life and act upon them. Measures of agency are central to understanding processes of empowerment and social, political, and economic change both locally and more broadly.